Produced by MSMEs in Gresik Regency: A Rate-All-That-Apply (RATA) Approach - Rahmania Shafa; Jariyah; Yunita Satya Pratiwi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Seasoned tempeh chips are a specialty product of Gresik Regency, with variations in spice formulations and raw materials among micro, small, and medium-sized enterprises (MSMEs) resulting in distinct sensory profiles. This study aimed to describe the sensory profiles of seasoned tempeh chips produced by MSMEs in Gresik Regency using the Rate-All-That-Apply (RATA) method and to determine the most preferred sample through a hedonic test. Significant differences were found in the attributes of yellow, brown, and golden-brown color, spicy aroma, crisp texture, spicy and sweet taste, lingering spiciness, and lingering sweetness. Samples 143 and 264 were characterized by spicy aroma and yellow color; sample 352 by spicy and oily sensations; sample 721 by crisp texture, brown color, and savory-salty taste; and sample 958 by fried, nutty, crisp, golden-brown, and sweet characteristics. Principal Component Analysis (PCA) explained 63.48% of the total sensory variability. Preference mapping indicated that sample 143 had the highest consumer preference (80–100%) and was primarily associated with savory and spicy aroma attributes, suggesting that these characteristics contributed most strongly to overall consumer liking. Contribution to Sustainable Development Goals (SDGs): SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation and Infrastructure